Composing compound libraries for hit discovery – rationality-driven preselection or random choice by structural diversity?. (December 2014) - Weidel, Elisabeth; Negri, Matthias; Empting, Martin; Hinsberger, Stefan; Hartmann, Rolf W
Aims: In order to identify new scaffolds for drug discovery, surface plasmon resonance is frequently used to screen structurally diverse libraries. Usually, hit rates are low and identification processes are time consuming. Hence, approaches which improve hit rates and, thus, reduce the library size are required.Methods: In this work, we studied three often used strategies for their applicability to identify inhibitors of PqsD. In two of them, target-specific aspects like inhibition of a homologous protein or predicted binding determined by virtual screening were used for compound preselection. Finally, a fragment library, covering a large chemical space, was screened and served as comparison.Results & Conclusion: Indeed, higher hit rates were observed for methods employing preselected libraries indicating that target-oriented compound selection provides a time-effective alternative.